Pendekatan Matematika Realistik dengan Bantuan Puzzle Pecahan untuk Siswa Sekolah Dasar - Achmad Firdaus (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2018)
There are still many students who have difficulties in learning fractions, because instructional is often delivered with abstract which is dominated by formal methods. Therefore, a new approach is needed, accompanied by adequate learning media to overcome the problems mentioned above. A realistic mathematical approach with the help of fractional puzzles was designed to help students to explain the abstract situations of a problem into a realistic form then developed to direct students to mathematically search solutions. The place of this study was in SD al Muslim Tambun with the research subjects of the fourth grade students of Ibnu Rusyd 2015/2016 Academic Year as many as 28 students. This is a Class Action Research with 2 trial cycles. The data was analyzed by comparing conventional techniques without learning media with realistic mathematical approaches with the help of fractional puzzles. The results shows that in the first cycle experiment there was an increase in the average value of learning outcomes of 15.64% with an average grade of 75.4. Then in the second cycle experiment there was an increase in the average value of student learning outcomes by 23.31% with an average grade value of 80.4. It can be concluded that the realistic mathematical approach with the help of fractional puzzles can increase the value of student learning outcomes in fraction addition material with the same denominator in elementary school.